Discontinuation of anti-VEGF cancer therapy promotes metastasis through a liver revascularization mechanism - Yunlong Yang (Nature Portfolio, 2016)
Anti-VEGF therapy often produces limited beneficial effects in cancer patients. Here, the authors show that discontinuation of anti-VEGF cancer therapy in xenografts-bearing mice increases cancer cells extravasation and intravasation in liver through the host-derived VEGF.